2017
DOI: 10.3390/en10122105
|View full text |Cite
|
Sign up to set email alerts
|

Positioning and Imaging Detection of Corona Discharge in Air with Double Helix Acoustic Sensors Array

Abstract: Corona discharge could be a serious hazard to the outdoor insulation of a high-voltage (HV) system and also is an important detection issue for insulation status diagnosis. In this study, a double-helix-ultrasonic-array (DHUA) sensor was developed for corona positioning, which showed a good sensitivity to the ultrasonic signal originating from corona discharge and a satisfied directional response in static beam patterns. Based on the matting-based image fusion method, the acoustic intensity matrix was fused to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The experimentally obtained absolute lateral error dependence on observation angle α is summarized in Table 4 and presented in Figure 11. It can be observed that the distance and the angle dependent lateral error in all cases does not exceed more than 0.15 m. While the works presented by other research groups demonstrate lateral source positioning errors of 5% [32], in this case the estimated lateral error is about 1.3% at 8 m. At such a distance, the experimental time delay between system channels 1 and 2 is ∆t = 84.2 µs at inter-element distance of 60 cm. It can be expected that at 30 m distance, which was used by other authors, the delay would be ∆t = 17.5 µs, which is still an easily measurable value.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…The experimentally obtained absolute lateral error dependence on observation angle α is summarized in Table 4 and presented in Figure 11. It can be observed that the distance and the angle dependent lateral error in all cases does not exceed more than 0.15 m. While the works presented by other research groups demonstrate lateral source positioning errors of 5% [32], in this case the estimated lateral error is about 1.3% at 8 m. At such a distance, the experimental time delay between system channels 1 and 2 is ∆t = 84.2 µs at inter-element distance of 60 cm. It can be expected that at 30 m distance, which was used by other authors, the delay would be ∆t = 17.5 µs, which is still an easily measurable value.…”
Section: Resultsmentioning
confidence: 60%
“…This introduces additional challenges, such as high transmission losses of acoustic signals, noise and multiple reflections within transformer substation, relatively short inspection distances and increased discharge source positioning errors. Among the attempts to detect and localize corona discharge, Dong et al [32] used a fusion of ultrasonic measurement and ultra-violet imaging to visualize the corona source locations in optical views with an angular error of 5.32% at 30 m distance.…”
Section: Introductionmentioning
confidence: 99%
“…It can provide a more intuitive and convenient way for the diagnosis of insulation status, which has a wide application prospect [ 22 ]. Dong et al propose an ultrasonic sensor array with 31 sensors arranged in a double-helix arrangement, and use a high-resolution spatial spectrum estimation method combined with an image fusion technique to locate the corona discharge in the outdoor insulation, which has an angular error of 5.32% at 30 m distance [ 23 ]. Yu et al propose an improved near-field acoustic holography (NAH) algorithm to visualize the measured sound field in order to locate the audible sound caused by transformer discharge faults [ 24 ].…”
Section: Introductionmentioning
confidence: 99%